After Eden a graphic novel - Arre, Arnold (Chamber Shell Publishing Inc., 2016)
"When two people first fall in live, they feel like the whole world revolves around their relationship. Like Adam and Eve, they feel like a Garden of Eden was created just for them. And when they fight or break up, it feels like every decision they made about each other forever changed the world for the worst. But what if it wasn't just a feeling? What if divine forces were literally placing the fate of the world on certain relationships? That's exactly what happens to Jon and Celine, recently reacquainted childhood friends who enter a whirlwind romance. They don't realize it, but angels and demons have wagered control of the world on the outcome of their relationship. It doesn't help that Jon's friends Greg and Mike team up with Celine's friends Lea and Cathy to try to break the up in order to bring things back to the old status quo, and to prevent the couple from playing matchmaker with them. This is not only puts Jon and Celine's relationship to the test, but the very fate of love in the world to hang in the balance." -- Provided by publisher